(untitled) (Forum Penelitian Agro Ekonomi, 2016)
Farmer’s empowerment through formal organization is very important in Indonesia, but its achievement is quite low. It is the state desire to formally organize the farmers and in contrary, the market tend to see the farmers, individually or in groups, to efficiently behave. Through the new institutionalism approach, such behavior could be understood on why and how the farmers organize themselves. This approach has been successfully overcome many limitations embedded in the previous approaches. With this new approach, perception on the farmer’s behavior is an awareness act and logically acceptable according to their socio-political context and various potential they have. This paper aims to describe various study results and expert thoughts on the concept and theory of “institution” and “organization”. According to the new institutionalism approach, the development of farmer’s organization need to consider principles that the formal organization is an option, give priority to function rather than bureaucracy administration, organization as a tool, reward based on farmer’s rasionality, and empowerment of farmer’s vertical relations is necessary.